In vitro Evaluation of Cytotoxic and Thrombolytic Activities of Oroxylum indicum (Linn.) (Bangladesh Pharmaceutical Journal, 2015)
Oroxylum indicum is a species of flowering plant belonging to the family Bignoniaceae and have many medicinal properties which prompted us to evaluate its possible thrombolytic and cytotoxic activities. A quick and rapid methodology was applied to find out the thrombolytic effect of the methanol extract of leaves of O. indicum. Streptokinase and water were employed as a positive and negative control, respectively. Thrombolytic effect was expressed as percentage of clot lysis. O. indicum, streptokinase and water demonstrated 23.69 ± 6.97%, 78.41 ± 0.366% and 5.19 ± 0.241% clot lysis, respectively. Cytotoxic property was evaluated by the brine shrimp lethality bioassay and the result was expressed as LC50. In this study, DMSO was used as solvent and vincristine sulphate as positive control. The extract showed cytotoxicity against brine shrimp nauplii and the calculated LC50 of O. indicum and vincristine sulphate were 251.2 ?g/ml and 5.2 ?g/ml, respectively. Due to the cytotoxic and thrombolytic activities, O. indicum may be regarded as a promising candidate for natural anticancer agent and should be subjected to purification processes for useful therapeutic drugs. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22319 Bangladesh Pharmaceutical Journal 17(1): 70-74, 2014